Intercropping with faba bean under appropriate row configuration increases root yield and active ingredient content of Codonopsis pilosula - Huang, Gaojian; Qin, Xingyu; Chen, Ziyu; Miao, Huifeng; Yang, Zhiping; Zhang, Qiang; Xing, Yi (Frontiers in Plant Science, 2025)
Continuous cultivation of the medicinal herb Codonopsis pilosula (C. pilosula) declines root yield and active ingredient content. Scientific and reasonable intercropping patterns can improve yield and active ingredient accumulation. However, how intercropping systems affect root yield and active ingredient content of C.pilosula is still poorly understood. We conducted a field experiment with four treatments, including monoculture C. pilosula (MC), one row of C. pilosula intercropping with one row of faba bean (IC1), two rows of C. pilosula intercropping with one row of faba bean (IC2), and four rows of C. pilosula intercropping with one row of faba bean (IC3), to explore the response of leaf traits, root yield, and active ingredient content of C. pilosula to cropping patterns. The results showed that intercropping significantly increased the root yield of C. pilosula by 7.0-18.7%, lobetyolin yield by 8.6-25.2%, atractylenolide III yield by 34.2-54.0%, and syringin yield by 31.1-53.4% compared to monoculture, and the largest yield advantage occurred in IC2. The results also showed that intercropping significantly improves leaf size, net photosynthetic rate, and C metabolism enzyme activity of C. pilosula. Correlation analysis and partial least squares path model showed that improved root and active ingredient yield in intercropping can be attributed to enhanced leaf photosynthesis and C metabolism, indicating that appropriate row configuration in C. pilosula/faba bean intercropping system could increase the yield of C. pilosula by enhancing light use efficiency. These findings suggest that two rows of C. pilosula intercropping with one row of faba bean is a promising approach to establishing a high-yield and sustainable C. pilosula agroecosystem.